The cloud book - DePaola, Tomie, 1934- (New York : Holiday House, 1975)
Introduces the ten most common types of clouds, the myths that have been inspired by their shapes, and what they indicate about the weather.
Includes index.
Booklist
School Library Journal
Wilson's Children
Appraisal-Science Books for Young People, April 2012
Booklist, April 2012
Keywords: Clouds -- Juvenile literature; Clouds; Clouds